CaMKII binding to GluN2B is differentially affected by macromolecular crowding reagents. - Dayton J Goodell; Tatiana A Eliseeva; Steven J Coultrap; K Ulrich Bayer (PLoS ONE)
Binding of the Ca2+/calmodulin(CaM)-dependent protein kinase II (CaMKII) to the NMDA-type glutamate receptor (NMDAR) subunit GluN2B controls long-term potentiation (LTP), a form of synaptic plasticity thought to underlie learning and memory. Regulation of this interaction is well-studied biochemically, but not under conditions that mimic the macromolecular crowding found within cells. Notably, previous molecular crowding experiments with lysozyme indicated an effect on the CaMKII holoenzyme conformation. Here, we found that the effect of molecular crowding on Ca2+/CaM-induced CaMKII binding to immobilized GluN2B in vitro depended on the specific crowding reagent. While binding was reduced by lysozyme, it was enhanced by BSA. The ATP content in the BSA preparation caused CaMKII autophosphorylation at T286 during the binding reaction; however, enhanced binding was also observed when autophosphorylation was blocked. Importantly, the positive regulation by nucleotide and BSA (as well as other macromolecular crowding reagents) did not alleviate the requirement for CaMKII stimulation to induce GluN2B binding. The differential effect of lysozyme (14 kDa) and BSA (66 kDa) was not due to size difference, as both dextran-10 and dextran-70 enhanced binding. By contrast, crowding with immunoglobulin G (IgG) reduced binding. Notably, lysozyme and IgG but not BSA directly bound to Ca2+/CaM in an overlay assay, suggesting a competition of lysozyme and IgG with the Ca2+/CaM-stimulus that induces CaMKII/GluN2B binding. However, lysozyme negatively regulated binding even when it was instead induced by CaMKII T286 phosphorylation. Alternative modes of competition would be with CaMKII or GluN2B, and the negative effects of lysozyme and IgG indeed also correlated with specific or non-specific binding to the immobilized GluN2B. Thus, the effect of any specific crowding reagent can differ, depending on its additional direct effects on CaMKII/GluN2B binding. However, the results of this study also indicate that, in principle, macromolecular crowding enhances CaMKII binding to GluN2B.